On the study of some singular integral equations - بن علي ذكرى -بكاري مروه (university of eloued جامعة الوادي, 2024)
في هذه المذكرة قمنا بدراسة بعض المعادلات التكاملية الشاذة. تتكون هذه الاطروحة من ثلاثة فصول رئيسية. وقد عرفنا في الفصل الأول المعادلة التكاملة وأنواعها وحلولها. وفي الفصل الثاني تناولنا أنواع المعادلات التكاملية الشاذة ومسألة هابيل والمعادلات التكاملية الضعيفة. أما الفصل الأخير فقد خصص لحلول المعادلات التكاملية باستخدام التحليل المركب. وفي الختام نأمل أن نكون قد وفقنا في تقديم وكتابة هذه الأطروحة .In this thesis, we have studied some singular integral equations. This thesis consists of three main chapters. In the first chapter, we have defined the integral equation, its types, and solutions. In the second chapter, we discussed the types of singular integral equations, the Abel problem, and weak integral equations. The final chapter is dedicated to the solutions of integral equations using complex analysis. In conclusion, we hope that we have succeeded in presenting and writing this thesis.
مدكرة ماستر رياضيات
Keywords: معادلة فريد هولم التكاملية ، معادلة فولتيرا التكاملية ، معادلة التكامل الشاذة ، النواة ، النقطة الشاذة; Fredholm integral equation; Volterra integral equation; Singular integral equation; Kernel; Singular point.